Aristocratic libraries in Slovakia – status, research, history - Sibylová Michaela (Grupa Cogito, 2021)
The author has divided her article into two parts. The first part describes the status and research of aristocratic libraries in Slovakia. For a certain period, these libraries occupied an underappreciated place in the history of book culture in Slovakia. The socialist ideology of the ruling regime allowed their collections (with a few exceptions) to be merged with those of public libraries and archives. The author describes the events that affected these libraries during and particularly after the end of World War II and which harmed the current disarrayed state and level of research. Over the past decades, there has been increased interest in the history of aristocratic libraries, as evidenced by multiple scientific conferences, exhibitions and publications. The second part of the article is devoted to a brief history of the best-known aristocratic libraries that were founded and operated in the territory of today’s Slovakia. From the times of humanism, there are the book collections of the Thurzó family and the Zay family, leading Austro-Hungarian noble families, and the library of the bishop of Nitra, Zakariás Mossóczy. An example of a Baroque library is the Pálffy Library at Červený Kameň Castle. The Enlightenment period is represented by the Andrássy family libraries in the Betliar manor and the Apponyi family in Oponice.